Characteristic of New Solid-Phase Extraction Sorbent: Activated Carbon Prepared from Rice Husks under Base Treated Condition - Afrida Kurnia Putri; Wang-Hsien Ding; Han-Wen Kuo (Chemistry Department, The University of Brawijaya, 2012)
A characterization of activated carbon (ACs) prepared from rice husks (RHs) under base treated condition as a new sorbent for solid-phase extraction (SPE) to extract 4-nonylphenol isomers (4-NPs) in water samples has been done. The ACs prepared from RHs usually exhibits low specific surface area due to its high ash content, but in case of its application for SPE, there are other factors need to be considered, such as the existence of functional groups inside the sorbent, that can enhance interaction of non-polar sorbent with analyte in the water matrices. In this case, silanol groups from ash content may affect the extraction efficiency for 4-NPs. The ACs made from RHs were chemically impregnated with ZnCl2 and carbonized at 800oC. To investigate the role of silica, three types of ACs were prepared, i.e., untreated ACs (AC–Si, contain silica), base treated ACs (AC–B–Si, remain some silica inside), and ACs made by base treated RHs (AC–B, no silica), the surface area obtained from these treatments were 1352 m2/g, 1666 m2/g, and 1712m2/g respectively. ACs made by base treatment has the highest surface area (related to BET), which indicat that silica removal process promotes the formation of open pore system on ACs and enhances the surface area of ACs. However, extraction efficiency measured by GC-MS in SPE process showed the reversal trends (i.e., AC–Si= 32.08%, AC–B–Si= 82.63%, AC–B=51.78%), among them the AC–B–Si sorbent reveal the best performance in SPE process. It is indicated that although silica usually exhibits low specific surface area, but control presence of silica as a polar functional group has a positive influence in the interaction between non-polar sorbent and 4-NPs.